2019
DOI: 10.1177/0095399719878727
|View full text |Cite
|
Sign up to set email alerts
|

Can Administrative Capacity Address Wicked Problems? Evidence From the Frontlines of the American Opioid Crisis

Abstract: What is the link between administrative capacity and wicked problems? Previous literature links capacity to standardized performance outputs, but little is known on the link between capacity and highly complex policy settings. This study examines health outcomes of the opioid crisis—a wicked problem with interdependencies across different drugs with multiple legal and illegal pathways for abuse and dependence. If capacity matters for wicked problems, administrative action should decompose the larger wicked pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Finally, we predict that administrative capacity will moderate the relationship between role perception and program access (McCrea, 2020). This expectation is grounded in previous studies that have found that "bureaucrats are constrained in what their agency considers efficient and what the program rules require .…”
Section: Slbs and The Strategic Use Of Discretionmentioning
confidence: 68%
“…Finally, we predict that administrative capacity will moderate the relationship between role perception and program access (McCrea, 2020). This expectation is grounded in previous studies that have found that "bureaucrats are constrained in what their agency considers efficient and what the program rules require .…”
Section: Slbs and The Strategic Use Of Discretionmentioning
confidence: 68%
“…It also reflects the vast literature on traditional management challenges in the Latin American context, which highlights problems of corruption and a lack of transparency across policy fields (de Viteri Vázquez & Bjørnskov, 2020; López & Moreno, 2010; Rotberg, 2019; Schwartz, 2021). Moreover, the results of this demonstration case may suggest extending wicked problem scholars' focus on collaborative governance approaches (Duit & Galaz, 2008; Head, 2019) to rigorous analysis of policy capacity in addressing wicked environmental problems (McCrea, 2020; Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…Step 1, description, may be frustrated by social complexity (Conklin, 2005), diversity (Head, 2008), or inflexible analysts who impose preconceived frameworks (Coyne, 2005). Step 2, prediction, may be thwarted by ambiguity and interdependency (Termeer et al, 2015) and interconnectivity (McCrea, 2020). Step 3, evaluation, is prevented by the lack of any consensus about the social good (Pesch & Vermaas, 2020; Rittel & Webber, 1973).…”
Section: The Problem Specifiedmentioning
confidence: 99%